Developed trigger mechanisms to improve crush force efficiency of aluminium tubes - Rai, V.; Ghasemnejad, Hessam; Watson, James W.; Gonzalez-Domingo, J. A.; Webb, Phil (Elsevier, 2019)
This paper aims to investigate the effect of a trigger mechanism on the crush force efficiency of aluminium tubular absorbers. Various trigger mechanisms such as cut-out holes, circumferential notch and end-fillet, were studied using the validated numerical model. Initially, tubes made of aluminium displayed better crashworthiness behaviour when compared with steel tubes based on numerical and experimental results. Then the trigger mechanism consisting of three cut-out holes was found more efficient than the ones with an end fillet and a circumferential notch based on a comparative study. According to these results, the developed trigger mechanisms have a significant change in crashworthiness performance of tubular absorbers. Crush force efficiency was doubled with the help of this trigger mechanism while stroke efficiency and specific energy absorptions were reduced by 4% and 15% respectively.
Keywords: Crash; Trigger mechanisms; Circular tubes; Cut-out